Modeling of Axial Flow between Eccentric Cylinders - Jane, Labadin; A. G., Walton (2006)
The study of thread annular flow is motivated due to the fact that thread injection is a promising method for placing medical implants within the human body with minimum surgical trauma. The porous thread is stored on a spool and injected within a fluid by applying a pressure gradient. The injection process must be smooth, and lateral deviations of the thread are undesirable. This paper presents a mathematical modeling of the problem and discusses preliminary findings concerning the nature of the basic flow.